Photoluminescence-structure relationships in ormosils for integrated optical devices - Sá Ferreira, Rute; Molina, Celso; Dahmouche, Karim [UNESP]; Ribeiro, Sidney [UNESP]; Gonçalves, Rogéria R.; De Zea Bermudez, Verónica; Carlos, Luís Dias (Springer Nature, 2005)
Planar waveguides with low losses in the infrared (from 0.6-1.1 dB/cm) were prepared with sol-gel derived poly(oxyethylene)/siloxane hybrid doped with zirconium(IV) n-propoxide (ZPO) and methacryloxypropyltrimethoxysilane (MAPTMS). The doped nanohybrids were characterized by small angle X-ray scattering, 29Si nuclear magnetic resonance and photoluminescence spectroscopy and compared with the undoped hybrid material. The results indicate an effective interaction between the zirconium particles and the siliceous nanodomains. © 2005 Materials Research Socicty.
Keywords: Doping (additives); Nuclear magnetic resonance; Sol-gels; X ray scattering; Ormosils; Planar waveguides; Zirconium particles; Materials science